Didactics Transposition in Mathematics Learning that Facilitates Students' Statistical Literacy - Wijayanti, Palupi Sri; Dasari, Dadan (Proceeding International Conference on Mathematics and Learning Research, 2024)
Didactic transposition is the process of transferring knowledge from scientific sources to experts, which is then used by teachers in the learning process in educational units. This study aims to describe the use of didactic transposition as a means of student learning and mathematics learning that facilitates students' statistical literacy. This type of research is qualitative research with the summative content analysis method. The data source used comes from literature studies indexed by Scopus, both journals and international conference proceedings. The data analysis technique uses four stages, namely: selecting, comparing, combining, and sorting until relevant meanings are found in knowledge related to didactic transposition and statistical literacy. The results of the study of the literature of relevant Scopus-indexed journals stated that the use of didactic transposition as a means of learning for students that facilitates their statistical literacy can increase enthusiasm in learning mathematics and have an impact on the ease of students understanding what is conveyed by the teacher.